Oocyte Cryopreservation in Emergency Situations: Perspectives and Reality - Yurchuk, Taisiia; Petrushko, Maryna; Fuller, Barry; Goltsev, Anatoliy (EMJ Repro Health. 2020;6[1]:54-62, 2020)
Increased incidence of global recorded cancer, unforeseen circumstances in assisted reproductive technology, a pandemic situation, and surgical interventions which can cause impairment of the reproductive system all necessitate urgent fertility preservation. Unfortunately, the application of successfully developed methods for oocyte and embryo cryopreservation is not possible in some situations because of contraindications for inducing superovulation, inability to delay other treatments, or in the case of prepubertal patients; in these cases, cryopreservation of ovarian tissue may be an alternative method. Despite current achievements in ovarian tissue low-temperature preservation, only 130 children have been born using this method. Further development of this technique and methods for in vitro maturation of immature oocytes, following their cryopreservation and use in assisted reproductive technology, as well as a differentiated approach for the selection of mature oocytes obtained without preliminary superovulation are needed. This review outlines the modern achievements and future prospects of female fertility preservation in emergency situations by cryopreservation of oocytes with different quality and maturity states.
Yurchuk T, Petrushko M, Fuller B, Goltsev A. Oocyte cryopreservation in emergency situations: perspectives and reality. EMJ Repro Health. 2020;6[1]:54-62. https://doi.org/10.33590/emjreprohealth/20-00081
Keywords: Cancer; immature oocyte; oocyte in vitro maturation; urgent fertility preservation; vitrification